2006
DOI: 10.1111/j.1749-7345.2006.00057.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pond Production Efficiency, Fatty Acid Profiles, and Contaminants in Litopenaeus vannamei Fed Organic Plant‐based and Fish‐meal‐based Diets

Abstract: Reduction or elimination of fish meal and fish oil from aquaculture diets can help to reduce the potential for contamination and dependence of the industry on pelagic fisheries while improving economic competitiveness. However, fish oil provides important omega‐3 (n‐3) fatty acids (FAs) essential to shrimp health and beneficial to humans. This study evaluated an organic, plant‐based diet formulated to replace fish meal and fish oil with plant proteins and docosahexaenoic acid (DHA) produced by algal fermentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 27 publications
(31 reference statements)
1
36
0
2
Order By: Relevance
“…It was also reported that 80% FM could be replaced by co-extruded soybean and poultry by-product meal supplemented with egg in indoor recirculating water system (Davis and Arnold 2000). Likewise, other researchers suggested different inclusion levels of FM in the diet of whiteleg shrimp culture in different conditions (Samocha et al 2004a;Browdy et al 2006;Patnaik et al 2006;Amaya et al 2007). This is while in marine shrimp diets, higher levels of dietary SBM usually resulted in lower growth (Akiyama 1990;Floreto et al 2000).…”
Section: Discussionmentioning
confidence: 94%
“…It was also reported that 80% FM could be replaced by co-extruded soybean and poultry by-product meal supplemented with egg in indoor recirculating water system (Davis and Arnold 2000). Likewise, other researchers suggested different inclusion levels of FM in the diet of whiteleg shrimp culture in different conditions (Samocha et al 2004a;Browdy et al 2006;Patnaik et al 2006;Amaya et al 2007). This is while in marine shrimp diets, higher levels of dietary SBM usually resulted in lower growth (Akiyama 1990;Floreto et al 2000).…”
Section: Discussionmentioning
confidence: 94%
“…These single-celled organisms are commonly found in marine and other saline environments and are a potential source of oil for aquaculture [17e21], as they produce lipids with high levels of eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), and arachidonic acid (ARA) [22e24]. Studies have demonstrated that coextruded soybean and poultry byproduct meal and a commercially available source of thraustochytrid oil from the species Schizochytrium is a strong potential candidate for fishmeal and fish oil replacement in shrimp feed [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…This deficiency could be covered by very small amounts of fish oil, squid meal and liquid fish soluble, which not only improved palatability, but also acted as a full or superior equivalent in shrimp production grow‐out feed compared to conventional FM‐based diets (Browdy et al . ). On the other hand, Moreno‐Arias et al .…”
Section: Traditional Sourcesmentioning
confidence: 99%
“…The consulted bibliography shows that although vegetables can substitute high FM levels (50%), FM cannot be totally replaced without including some animal marine protein sources (Browdy et al . ). Most of the diets cited in Table include a low percentage of squid meal or some other marine source to guarantee a minimum marine protein input.…”
Section: Traditional Sourcesmentioning
confidence: 99%